The use of artificial intelligence and audit quality: An analysis from the perspectives of external auditors in the UAE - Nora Azima Noordin; Khaled Hussainey; Ahmad Faisal Hayek (Journal of Risk and Financial Management, 2022)
This paper aims to explore external auditors' perception of the use of artificial intelligence (AI) in the United Arab Emirates (UAE). It investigates whether there is a perception among external auditors toward the contribution of AI to audit quality. It also aims to test whether the perception of AI usage and its impact on audit quality differs between local and international external auditors. Data were collected using an online survey from 22 local and 41 international audit firms to achieve these research objectives. Participants were either the auditing manager, audit partners, senior auditors or other personnel who may have experience in the field of accounting and auditing. To test our hypotheses, data analysis was undertaken using reliability and validity tests, descriptive analysis and independent samples t-test. We found that the analysis shows that there is a non-significant difference in the perceived contribution of AI to audit quality between local and international audit firms. All the audit firms, whether local or international, have equal perceived contributions with regard to the audit quality.
Keywords: 650; artificial intelligence; audit quality; contribution; external auditors; external auditors’ perceptions